THE NATIONAL IDEA AND NATIONAL IDEOLOGY IN THE SUSTAINABILITY OF ETHNOCULTURAL IDENTITY - ALLAHVERDIEV, Kenan (CENTRAL ASIA AND THE CAUCASUS, 2015)
The author investigates the correlative ties between the categories “national idea” and “national ideology” and their impact on the ethnocultural identity of peoples in the context of the contradictory processes at the current stage of globalization.